2022
DOI: 10.1002/pssb.202200368
|View full text |Cite
|
Sign up to set email alerts
|

Boron Arsenate Scaled‐Up: An Enhanced Nano‐Mimicking Mechanical Metamaterial

Abstract: Novel mechanical metamaterials inspired by single crystal boron arsenate built at the macroscale using conventional materials are presented and investigated through finite element simulations. It is shown that these mechanical metamaterials can mimic, to some extent, the properties of boron arsenate with the more robust rotating rigid‐units mechanism being excellently replicated and even made to operate more efficiently through modifications of the geometry of the mechanical metamaterial. It is also shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…The investigations suggest that already existing materials can prove to be a very useful source of information for the design of novel mechanical metamaterials. [ 4 ]…”
Section: Macroscopic Structuresmentioning
confidence: 99%
“…[27] In addition to the aforementioned rotating quadrilaterals, auxetic systems in the form of interconnected rotating triangles have been developed, such as equilateral triangles [28] and scalene triangles. [29] A comprehensive survey of these works has been reviewed by Grima-Cornish et al [30] . Shortly thereafter, auxetic systems based on combined quadrilaterals and triangles [31][32][33][34] as well as rotating and nonrotating quadrilaterals [35] were introduced.…”
Section: Introductionmentioning
confidence: 99%